Promising electron mobility and high thermal conductivity in Sc2CT2 (T = F, OH) MXenes. Issue 11 (2nd March 2016) - Zha, Xian-Hu; Zhou, Jie; Zhou, Yuhong; Huang, Qing; He, Jian; Francisco, Joseph S.; Luo, Kan; Du, Shiyu
Abstract : The MXenes Sc2 CT2 (T = F, OH) show promising electron mobility and high thermal conductivity from first-principles calculations, suitable for electronic device applications. Abstract : MXenes, the new 2D transition metal carbides and nitrides, have recently attracted extensive attention due to their diverse applications and excellent performances. However, the thermal and electrical properties of most MXene materials are yet to be studied. In this work, we investigate the electrical and thermal properties of semiconducting Sc2 CT2 (T = F, OH) MXenes using first-principles calculations. Both of the Sc2 CT2 (T = F, OH) MXenes are determined to show excellent carrier mobilities. The electron mobility in the Sc2 CF2 MXene is found to be strongly anisotropic at room temperature, with values of 5.03 × 10 3 and 1.07 × 10 3 cm 2 V −1 s −1 in the zigzag and armchair directions, respectively. The predicted electron mobility in the zigzag direction of the Sc2 CF2 is nearly four-fold that in the armchair direction of the promising semiconductor phosphorene. In contrast to Sc2 CF2, Sc2 C(OH)2 presents approximately isotropic electron mobility. The values at room temperature in the zigzag and armchair directions are calculated as 2.06 × 10 3 cm 2 V −1 s −1 and 2.19 × 10 3 cm 2 V −1 s −1, respectively. In regard to the thermal properties, the thermal conductivities of the Sc2 CT2 (T = F, OH) MXenes have been determined. The predicted values are higher than those of most metals and semiconducting low-dimensional materials, such as monolayer MoS2 and phosphorene. In particular, the room-temperature thermal conductivity along the Sc2 CF2 armchair direction has been determined to be as high as 472 W m −1 K −1 based on a flake length of 5 μm, which is even higher than that of the best traditional conductor silver. The corresponding value in the zigzag direction of Sc2 CF2 is calculated to be 178 W m −1 K −1 . The thermal conductivity in Sc2 C(OH)2 is less anisotropic and lower compared to that in Sc2 CF2 . The room-temperature value in the armchair (zigzag) direction is determined to be 173 W m −1 K −1 (107 W m −1 K −1 ). Based on their excellent electron mobilities and high thermal conductivities, both of the Sc2 CT2 (T = F, OH) MXenes could be promising candidate materials for the next generation of electronic devices.